Desenvolvimento brasileiro: o olhar de Caio Prado Junior na Revista Brasiliense (1955 1964) - Portella Junior, Onofre Alves (2012)
This research is a study about the Caio Prado Junior's perspective concerning brazilian development. It has as main focus the articles published by the author in Revista Brasiliense, a bimonthly periodic edited between September October of 1955 and January February of 1964. Caio Prado Junior was one of the magazine founders and a main collaborator author. His articles usually presented ample thematics, lying toward the magazine main caracteristc. The years between 1955 and 1964 are historiography characterized as the richest period about national debate. In the context of brazilian development issue Revista Brasiliense is absolutely contemporary. Caio Prados's deep analysis always deal with the conceptions of industrialization, dependency e nationalism. Linking all this aspects the author opposes the capitalism mode of production, international characterized, with a national premisse for development